Ivan Tavčar in njegova antisemitska narativa v kontekstu evropskega antisemitizma pred drugo svetovno vojno - Vičar, Branka (Studia Historica Slovenica, 2017)
In the first part, the paper presents Tavčar's liberal political conviction, on which his opposition to the labour movement was justified. Tavčar's anti-Semitic discourse is directly related to the struggle against the labour movement, but in this intertwinement Tavčar emphasized the former. A comparison is made between Tavčar's literary and publicist anti-Semitism in terms of the content of the anti-Semitic discourse and the degree of linguistic straightforwardness. Tavčar's publicist anti-Semitism is linked to a specific historical context, namely with the October Revolution in Russia. We can understand it, above all, as a political weapon, with which he tried to mobilize members of the middle socioeconomic class, who shared the anti-Semitic feeling, primarily as a way of resisting the communist class struggle.
Keywords: antisemitizem; delavsko gibanje; politična zgodovina; Slovenija; Tavčar, Ivan